IMPREVISIBILIDADE, BUROCRACIA E IMPROVISAÇÃO: ESTUDO DE CASO EM UMA UNIVERSIDADE PÚBLICA FEDERAL. - Cardoso, Antonio Augusto Brion (2022)
Public universities have characteristics that make their management a challenge. The structural complexity, allied to the rigidity of norms and rules that govern the use of public resources, contribute to these institutions being slow in responding to the demands of the environment. In crisis situations, this feature becomes even more challenging as it requires quick decisions and actions. In this context, plans, routines and standard procedures prove to be inefficient to meet urgent and unexpected demands, demanding alternative solutions from public managers that are, at the same time, in line with rigid institutional precepts on the use of resources. Thus, given the need for agility and some inefficiency - arising from the excessive rationality of preestablished decision-making processes in public management - it is common for improvisations to manifest, whether of an extraordinary or infraordinary nature. This study examined how improvisation manifests itself in the performance of the university manager when reconciling rigid legal formalities and the use of financial, human and structural resources in urgent and unexpected demands. To this end, concepts of public management, improvisation and organizational complexity applied to a federal public university in the context of the Coronavirus pandemic were used. This is a qualitative research, whose data were collected through interviews and documents and were analyzed using the technique of narrative analysis and document analysis. Results pointed out that the crisis situation potentiated an additional challenge related to the use of resources, having as antecedent factors directly and indirectly related to the complex and bureaucratic structure of the university, such as the limitation imposed by the legislation for the use of resources, budget restriction, diversity of interests and the slowness caused by pre-established routines and procedures. On the other hand, other characteristics typical of the complexity of the analyzed context – such as the dynamicity of interactions, the agents' ability to adapt and learn – allowed quick and viable responses to the demands presented through the manifestation of improvisations. Improvisations - both of an extraordinary and infra-ordinary nature - proved to be essential to enable the use of resources, helping managers to deal with surprise, urgency and the exceptional. It was verified that the extraordinary and infraordinary improvisations generated learning, although the last of them only contributed to individual learning, which, given the rigidity of the rules and legislation for the use of resources, brings fear on the part of the agents, to act in a detached way. of the default. However, it was found that extraordinary improvisation promoted organizational learning, even contributing to changes in existing procedures and routines, in order to represent a virtuous circle resulting from the antecedent and consequent factors identified. Results allowed advancing in the representation of a possible behavior of improvisation in relation to learning – and unlearning – in the context of public universities, in particular, in a crisis situation.